The poetry of Jack Kerouac : Scattered poems ; The Scripture of the golden eternity ; Old angel midnight - Kerouac, Jack, 1922-1969 (Open Road Integrated Media, 2017)
From the iconic New York Times-bestselling author of On the Road: Three revolutionary collections of poetry in one volume. Rebelling against the dry rules and literary pretentiousness he perceived in early twentieth-century poetry, Jack Kerouac pioneered a poetic style informed by oral tradition and driven by concrete language with neither embellishment nor abstraction. In these three groundbreaking collections, the legendary Beat writer offers a spontaneous, uncensored perspective on everything from religion to the structure of language itself. Scattered Poems: Bringing together selections from literary journals and his private notebooks, Scattered Poems exemplifies Kerouac's innovative approach to language. Populated by hitchhikers, Chinese grocers, Buddhist saints, and cultural figures from Rimbaud to Harpo Marx, the poems evoke the primal and the sublime, the everyday and the metaphysical. The Scripture of the Golden Eternity: During an unexplained fainting spell, Kerouac experienced a flash of enlightenment. A student of Buddhist philosophy, he recognized the experience as "satori," a moment of life-changing epiphany. The knowledge he gained in that instant is expressed in this volume of sixty-six prose poems with language that is both precise and cryptic, mystical and plain. His vision proclaims, "There are not two of us here, reader and writer, but one golden eternity." Old Angel Midnight: A spontaneous writing project in the form of an extended prose poem, this sonorous and spiritually playful book is one of Kerouac's most boldly experimental works. Collected from five notebooks dating from 1956 to 1959-a time in which Kerouac was immersed in Buddhist theory-Old Angel Midnight captures the rhythms of the universe and secrets of the subconscious with stunning linguistic dexterity.